INITIAL CAPACITY OF BIOENERGETIC PRODUCTION FOR THE RECYCLING OF PLASTICS IN CABINDA, ANGOLA - David Muto Lubota; Tania Grancho Freitas; Divanize de Jesus Sambovo Landa; Juan Esteban Miño Valdés; Binko Mamade Toure (Revista Centro Azúcar, 2016)
In this paper, the study of the possibilities of the efficient use of forest residuals as raw  materials, for the production of bioenergetics that guarantees the operations of a plant  for the recycling of plastic residuals is exposed. In the study, a conceptual model and  the procedures for the assimilation of technologies of bioenergetic production, reported  in previous works, is validated (Muto et al., 2016). Due to their significance, it is  considered the uncertainty to the future changes with emphasis to the growth of the  demand of capacities of prosecution of urban solid wastes (USW) and the readiness of  the raw material. Suitable values of initial investment capabilities are determined for a  first step forward so that a second stage investor that increases capabilities must be run  at 6 years for initial investment executed capabilities. The first investment will recover  in 2.8 years.